Effect of Maternal Sildenafil Supplementation During Gestation on the Reproductive Performance of Sows/Gilts and Growth Performance of Neonatal Piglets - Wang, Yue; Qin, Yusheng; Zhao, Wei; Yao, Fusheng; Wang, Wenjing; Hu, Xiao; Cheng, Linghua; An, Lei; Tian, Jianhui (Frontiers in Veterinary Science, 2022)
Reproductive performance of sows or gilts is of prime importance for economic benefits in pig farming, and is highly associated with uterine characteristics. Among these, uterine blood flow is the critical determinant for pregnancy outcomes. Thus, the aim of this study is to determine whether maternal supplementation with sildenafil, a stimulator of vascular development and functions, during gestation can improve litter performance of sows/gilts and growth performance of neonatal piglets. Sows were randomly assigned to different groups receiving a basal diet (control group) or diets supplemented with sildenafil at various stages of gestation, respectively. At parturition, total number of piglets born per litter, number of piglets born alive or dead, average birth weight, number of weaned piglets and average weaning weights were recorded and analyzed. Sildenafil supplementation throughout gestation (GD 0–110) increased both litter size and average birth weight. To reduce the cost of extended sildenafil supplementation, time-phased strategies were further tested. Sildenafil supplementation during the early gestation (GD 0–30), mid gestation (GD 30–80) and the late gestation (GD 80–110) partially improve litter performance. Notably, sows fed sildenafil supplementation from middle to late gestation (GD 30–110) significantly improved litter performance to levels comparable to those in the sows supplemented with sildenafil throughout whole gestation. Together, our results showed that maternal sildenafil supplementation during gestation can effectively improve pregnancy outcomes of sows and gilts, and enhance growth performance of neonatal piglets, thus providing a promising and practical intervention strategy for improving reproductive management in pig farming.